Arabidopsis thaliana genes with codon usage bias similar to that of B. amyloliquefaciens are involved in the regulation of A. thaliana adaptation to high calcium stress by B. amyloliquefaciens - Li, Fei; Zhang, Qinye; Lu, Yuntong; Chen, Xiaoyan; Liu, Xing; Qiu, Xiangting; Gu, Yunying; Wang, Puchang; Liu, Jie (Frontiers in Plant Science, 2025)
IntroductionCodon usage bias (CUB) can influence host-microbe interactions and stress adaptation. In this study, we aimed to investigate how codon usage bias (CUB) similarity between Arabidopsis thaliana and Bacillus amyloliquefaciens influences their interaction and contributes to the adaptation of A. thaliana to high calcium stress.MethodsThe CUB indices of both species were computed, and genes with high correlations were identified. The transcriptome sequencing data of gene expression in A. thaliana cultured under normal and high calcium conditions, with and without B. amyloliquefaciens treatment was used to analyze the expression of A. thaliana genes with CUB similar to that of B. amyloliquefaciens in relation with the adaptation of A. thaliana to high calcium stress and the interaction between both organisms.ResultsWe identified 19210 A. thaliana genes with CUB similar to B. amyloliquefaciens and 95 B. amyloliquefaciens-responsive and calcium-responsive genes in A. thaliana, which were involved in transport, carbohydrate metabolism, and response to chemical, and cellular homeostasis. Differential expression analysis showed a total of 733 A. thaliana genes with CUB similar to B. amyloliquefaciens to be dysregulated, among which 47 changed when A. thaliana was cultivated in the presence of the B. amyloliquefaciens LZ04 strain, 643 under high calcium condition and 43 with calcium treatment and the presence of the B. amyloliquefaciens LZO4 strain. The gene ontology (GO) biological processes termed among others of response to endogenous stimulus, response to oxygen containing compound, response to organic substance, response to abiotic and biotic stimuli, response to stress, and response to light stimulus, regulation of hormone levels, response to nutrient levels, post-embryonic plant morphogenesis, metabolic process, cell growth.DiscussionThese findings highlight the importance of CUB in the interaction between A. thaliana and B. amyloliquefaciens as well as in the adaptation of A. thaliana to high calcium stress. They also show the underlying regulatory role of B. amyloliquefaciens, which could help develop new tactics for improving A. thaliana growth and yield in karst regions. A more elaborate analysis of the value of CUB in the interaction of these two organisms could assist in engineering host- sensitive micro-organism strains and enhance the microbial-based approaches for the improvement of A. thaliana growth and yield in such areas and for managing abiotic stress in crops.